Gopher Apple, Geobalanus oblongifolius Synonym: Licania michauxii - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Gopher apple occurs from the lower Florida peninsula northward to South Carolina westward to Louisiana in coastal dunes, sandhills, and disturbed areas such as roadsides. Gopher apple gets its name because gopher tortoises, along with other small mammals, eat their fruit. Gopher apple is an ideal groundcover for a coastal landscape with well-draining soil and a low pH (Gilman 2014). https://edis.ifas.ufl.edu/sg169